PENINGKATAN PRODUKTIVITAS MELALUI PENGEMBANGAN APLIKASI PPH 21 VOL. 1 PADA KKP TJARMADI DAN REKAN - Sheila Febriani Putri; Ria Zulkha Ermayda; Dhika Maha Putri; Hanjar Ikrima Nanda (Bajang Institute, 2023)
Taxes are contributions that are obligatory for citizens of the country. Tax is something that is coercive and is the main income of the state for the improvement and development of the country. Taxes consist of various types, one of which is Income Tax. Income Tax (PPh) Article 21 is a tax imposed on income for work, services or other activities which include wages, salaries, honoraria and the like. Where the PPh calculation is calculated using the self-assessment method so that the calculation often makes mistakes. This activity aims to develop the PPh Article 21 application so that the calculation of the tax to be paid can be more accurate. The Tax Consultant Office will work with vendors to make PPh Article 21 applications which are expected to be able to separate how many employees have income above PTKP and below PTKP (tax free). The result of this activity is the creation of the PPh Article 21 application related to a more accurate calculation of types of income and other additional income and deductions received by employees.